Combination of Ketepeng Cina (Cassia alata Linn) And Lidah Buaya Buaya (Aloe vera) As Antibacterial Agent Against Staphylococcus aureus And Pseudomonas aeruginosa - Cita Hanif Muflihah; Az Zahra Miftahul Husna; Aminah Fitriana Hamka (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Infection is one of the biggest health problems in Indonesia. Infection can be caused by pathogenic microorganisms such as Staphylococcus aureus and Pseudomonas aeruginosa. Treatment with antibiotics is the primary choice to manage infections caused by bacteria. Previous research showed that many plants have been tested for their antibacterial activity such as ketepeng cina (Cassia alata) and lidah buaya (Aloe vera). Cassia alata and Aloe vera alkaloids, flavonoids, anthraquinones, saponins, tannins contain similar active compounds as antimicrobials. Based on this, the purpose of this study was to determine the antibacterial activity of the combination of methanol extracts of C. alata and A. vera against S. aureus and P. aeruginosa bacteria. The antibacterial activity test was carried out using the Kirby-Bauer method. The single extract of C. alata and A. vera had the greatest antibacterial activity against S. aureus at a concentration of 10 mg/disk with zones of inhibition of 29.5±0.7 mm and 21.5±1.4 mm, respectively. The single antibacterial activity test of both extracts against P. aeruginosa bacteria showed no inhibition zone. The test results showed that the combination of 10 mg/disk C. alata methanol extract and 10 mg/disk Aloe vera could inhibit the growth of S. aureus with an average inhibition zone of 30.75±1.7 mm. However, the lower ratio of both extracts resulted in a likely antagonistic effect against S. aureus. Phytochemical screening tests showed that these two extracts had the same compounds, namely phenolics, flavonoids, anthraquinones. Contact bioautography showed that mainly phenolics, flavonoids, and anthraquinones were responsible in the antibacterial properties.